The FDA modernisation act 2.0: Bringing non-animal technologies to the regulatory table. Issue 4 (April 2023) - Stewart, Alastair; Denoyer, Delphine; Gao, Xumei; Toh, Yi-Chin
Highlights: The FDA modernisation Act 2.0 marks a game-changing legislation enabling drug registration without the absolute requirement for the use of animals in safety toxicology assessment. In silico methods are having a significant and growing impact on drug development. This act focusses our attention on new opportunities to embed microphysiological systems in the drug regulation pathway. Community drive away from animal usage, the three Rs and the cost and availability of animal studies can be identified as providing a push to complement the pull of improving MPS technologies. Abstract: The FDA modernisation Act 2.0 marks a game-changing legislation enabling drug registration without the absolute requirement for the use of animals in safety toxicology assessment. We discuss landmark developments in the legislation under which the FDA operates and consider the implications of this most recent chapter in the evolution of the drug regulation pathway, focussing on new opportunities to embed microphysiological systems.